Survival Is Not Enough: Zooming, Evolution, and the Future of Your Company - Seth Godin
The author of Permission Marketing explains how a fear of change and survival-level values are preventing many companies from becoming successful, revealing tactics that help businesses to embrace change. Simultaneous.